Spanish relief: summary of letter from Huddersfield Trades Council - Hargrave, G. ; Huddersfield Trades Council
037-0054-001 Trades Union Congress General Council CORRESPONDENCE. Extract from letter sent to Organisation Department. Name of Sender Mr. G. Hargrave, Huddersfield Trades Council, Address 41, Smith's Avenue, Marsh, Huddersfield. Date 26th August, 1937 Subject SPANISH RELIEF. "Huddersfield T. C. formed a Spanish Aid Committee, enlarged the same with the Mayor as Chairman. All political organisations are represented, all religious and many semi-public organisations. We have a home with 20 Spanish children and two adults. A town's house-to-house collection will take place next week; 22 offers of 10s. a week whilst the children are here have been promised. A public meeting with the Duchess of Athol as speaker raised £250 promises and £10 in collections, and in addition £42 has been collected in T. U. branches, workshop collections, etc., under the auspices of the National Joint Committee for Spanish Relief." HVT [SEE OVER FOR CONTINUATION. 292/946/37/54